Federally Overlooked Flood Risk Inequities in Houston, Texas: Novel Insights Based on Dasymetric Mapping and State-of-the-Art Flood Modeling. (2nd January 2023) - Flores, Aaron B.; Collins, Timothy W.; Grineski, Sara E.; Amodeo, Mike; Porter, Jeremy R.; Sampson, Christopher C.; Wing, Oliver
Abstract : In the United States, the Federal Emergency Management Agency (FEMA) delineates 100-year flood zones to define risks, regulate flood insurance premiums, and inform flood management. Evidence indicates that FEMA flood maps are incomplete, calling much of our current knowledge of U.S. flood hazard inequities into question. We use a state-of-the-art flood hazard model and census tract-level dasymetrically mapped sociodemographic data to examine flood risk inequities in the Greater Houston area, where increasingly frequent and damaging flood events are occurring. We innovate by analyzing federally overlooked 100-year flood risks (100-year flood zones delineated by the flood hazard model that are outside of FEMA 100-year flood zones). Results indicate that nearly 1 million Greater Houston residents live in federally overlooked 100-year flood zones. Black and Asian neighborhoods experience disproportionate risk in federally overlooked pluvial and fluvial flood zones, and Hispanic neighborhoods experience disproportionate risk in all federally overlooked zones (coastal, pluvial, and fluvial). High flood risk and the relative lack of protective resources in federally overlooked 100-year flood zones doubly jeopardizes racial and ethnic minority communities. Our findings and recent flood disasters suggest that future flood impacts in Greater Houston will be catastrophic and unjust unless FEMA revises their risk mapping and management approach to promote long-term public safety and social equity.